Squid-Inspired Tandem Repeat Proteins: Functional Fibers and Films - Pena-Francesch, Abdon; Demirel, Melik C. (Frontiers in Chemistry, 2019)
Production of repetitive polypeptides that comprise one or more tandem copies of a single unit with distinct amorphous and ordered regions have been an interest for the last couple of decades. Their molecular structure provides a rich architecture that can micro-phase-separate to form periodic nanostructures (e.g., lamellar and cylindrical repeating phases) with remarkable physicochemical properties that often exceed those of conventional synthetic polymers. Here, we review programmable design, structure, and properties of functional fibers and films from squid-inspired tandem repeat proteins, with applications in soft photonics and advanced textiles among others